2011
DOI: 10.1002/ijc.25848
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects dominate solid tumor response to treatment with combretastatin A‐4‐phosphate

Abstract: Vascular‐targeted therapeutics are increasingly used in the clinic. However, less is known about the direct response of tumor cells to these agents. We have developed a combretastatin‐A‐4‐phosphate (CA4P) resistant variant of SW1222 human colorectal carcinoma cells to examine the relative importance of vascular versus tumor cell targeting in the ultimate treatment response. SW1222Res cells were generated through exposure of wild‐type cells (SW1222WT) to increasing CA4P concentrations in vitro. Increased resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The anti-proliferative and pro-apoptotic properties displayed by these compounds are a proof-of-concept that the removal of CA4’s ethylene does not completely abolish in vitro anti-cancer activity. Importantly, the in vivo anti-cancer activity of CA4P has been shown to be largely independent of direct cancer cell targeting and instead is linked to its vascular damaging properties [ 50 ]. Thus, future characterization of MP5-G9 and MP5-59, as well as future biphenyl analogues, will need to involve animal models to evaluate the vascular damaging properties, bioavailability, and therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-proliferative and pro-apoptotic properties displayed by these compounds are a proof-of-concept that the removal of CA4’s ethylene does not completely abolish in vitro anti-cancer activity. Importantly, the in vivo anti-cancer activity of CA4P has been shown to be largely independent of direct cancer cell targeting and instead is linked to its vascular damaging properties [ 50 ]. Thus, future characterization of MP5-G9 and MP5-59, as well as future biphenyl analogues, will need to involve animal models to evaluate the vascular damaging properties, bioavailability, and therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Staining for p-ERM showed a CA4P-induced expression in tumour cells, as well as in tumour vasculature, that was blocked by Y27632 treatment. However, by utilizing SW1222 tumour cells developed to be resistant to CA4P, we have previously shown that the anti-tumour activity of CA4P in vivo is mediated by its tumour vascular effects, rather than by direct toxicity towards the tumour cells themselves (Lunt et al ., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…at 10 mL kg −1 in physiological saline. Mice were killed at 1, 3, 6 or 24 h after single-dose CA4P treatment (OxiGene Inc., San Francisco, CA, USA), at 100 mg kg −1 ; a previously determined effective dose for SW1222 tumours (Lunt et al ., 2011 ). Y27632 (Tocris Bioscience, Bristol, UK) was administered at the maximum tolerated dose in our mice of 50 mg kg −1 (unpublished data), either alone or 5 min before or 3 h after CA4P treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combretastatin-A4 phosphate CA4P, also named (Zybrestat ™ or fosbretabulin) is a tubulin depolymerizing agent, which has been shown to cause acute vascular disruption in tumors and has been extensively evaluated in mice, and rats and human clinical trials. 5,6,18–23 Reported side effects have included hypertension, tumor pain and occasional cardiovascular toxicity. 24 It has been stated that CA4P is tumor selective rather than specific and the lack of specificity for tumor endothelium was highlighted by studies showing a CA4-induced inhibition of the neovascularization of hyperplastic thyroids and retina, suggesting that CA4P may be relevant to the treatment of some non-cancer diseases.…”
Section: Introductionmentioning
confidence: 99%